(untitled) (Annals of Medical Research, 2021)
Aim: Intestinal lactase deficiency is the most common carbohydrate malabsorption and digestive disorder. If lactase deficiency coexists with gastrointestinal symptoms such as abdominal distension, flatulence, abdominal pain, diarrhea, vomiting and nausea, then the term “lactose intolerance” is used clinically. Uneasiness and excessive crying are frequently seen in the first 3 months of life and constitute nearly 20% of the patients who are referred to a pediatrician. This study aims to perform a retrospective analysis of the complaints of patients who have been diagnosed with lactose intolerance.Material and Methods: The files of patients, who were diagnosed with lactose intolerance between October 2017 and May 2018 in Defalife Hospital Pediatrics Outpatient Clinic, were retrospectively reviewed.Results: A total of 38 patients, consisting of 23 males and 15 females are included to the study. The mean age of the patients was 5.51±3.47 months (age range 1 to 18 months). 31% of the patients diagnosed with lactose intolerance were admitted to the hospital due to uneasiness and excessive crying, and all of the patients were previously diagnosed as having infantile colic. Conclusion: This study concludes that conducting tests for lactose intolerance might be beneficial in children that are presented to the hospital due to unexplained crying after the fourth month, at which time there is an expectation of seeing an improvement in colic behavior.